Thermoregulatory demands of elite professional America's Cup yacht racing - Neville, V.; Gant, N.; Folland, J. P. (Scandinavian Journal of Medicine & Science in Sports, 2010)
America's Cup yacht racing predominantly occurs during the summer months under hot and humid conditions, with athletes exposed to the environment for prolonged periods, and yet the thermoregulatory responses to competitive sailing are largely unappreciated. This study aimed to assess the thermoregulatory responses to elite professional big-boat yacht racing, according to crew position and upwind and downwind sailing. Intestinal (Tcore) and skin temperature, fluid balance and regional sweat compositions were measured in two America's Cup crews (n=32) during 100 min of racing. The environmental conditions were as follows: 32 °C, 52% RH and 5 m/s wind speed. Subjective race intensity was moderate. Bowmen recorded the greatest elevation in the heart rate (184 ± 10 beats/min) and Tcore (39.2 °C, P<0.01). Both heart rate and Tcore were higher during downwind sailing (P<0.001). Regional skin temperatures were significantly different according to site (P=0.05), with tibia being the lowest (33.3 ± 1.2 °C). The mean sweat loss during racing was 1.34 ± 0.58 L/h (range: 0.44-2.40 L/h), with bowmen experiencing the greatest loss of sweat (3.7 ± 0.9% of body mass). The mean fluid intake was highly correlated to sweat loss (r=0.74, P<0.001), with 72 ± 41% of sweat losses replaced. The mean sodium concentration of sweat was 27.2 ± 9.2 mmol/L (range: 12.0-43.5 mmol/L) and the total NaCl loss during sailing was 3.8 ± 2.4 g (range 0.7-10.0 g). America's Cup sailing is a demanding sport that presents considerable challenges to thermoregulation, fluid and electrolyte balance. Certain crew roles (bowmen) present an increased risk of developing exertional heat illness, and for the majority of crew downwind sailing results in greater thermal strain than upwind sailing - which may have implications for clothing selection and boat design.